مقاصد الشّريعة الإسلاميّة والسّياسيّة الشّرعيّة: (المفهوم والنّشأة والتّطوّر وبُعد كلّ منهما في الآخر) - Abdou Samad, D.; Abdul Rab Al- Qubaty, M. (Universiti Sains Islam Malaysia, 2024)
This study is intended to demonstrate that the science of Islamic politics is the basis of the principles of Islamic jurisprudence. It is also a vast field to highlight the reality of Maqasid on the level of activation and application. For if the fundamentals of fiqh, is the primary source to derive the rulings of calamities and the first custodian of what is known later by the knowledge of Maqasid, The study of Shari'ah policy was preceded by the level of application derived in reality. This research is conducted to study the problem of misusing the Maqasid in Shariah policy issues, which resulted in neglecting shar'i texts. The study aimed to explain the concept, origin and development of Maqasid and Islamic policies for judges, politicians, rulers and the like, and the relationship with the knowledge of Maqasid, with the presentation of an analytical study applied to samples of Islamic policy issues, using descriptive and analytical approach; And analyze the texts related to them, and then develop the appropriate relationship between them. The study achieved many results, the most important of which are: that political issues cannot be considered legitimate if they fail to observe the Maqasid in them. The science of Islamic politics is the core of Islamic jurisprudence in terms of the application of the rules of jurisprudence. Especially in later eras whose issues need careful consideration, sound thought and knowledge of the purposes of the law. And that the role of the policy of legitimacy is greatly improved when politicians seek to bring interests to the parish and to prevent the evils of more studies and awareness of Maqasid.